Perlindungan Hukum Terhadap Member Dalam Sistem Bisnis Multi Level Marketing - Rasni Rusli; Teng Berlianty; Marselo Valentino Geovani Pariela (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Multi Level Marketing or MLM is a direct or tiered marketing concept as formulated.Purposes of the Research: This study aims to determine and explain government supervision of MLM companies in Indonesia. Methods of the Research: This research is a normative legal research, using a law approach and a conceptual approach. Legal research materials include primary, secondary, tertiary data sources. Data collection techniques in the form of literature study. Techniques for analyzing data on legal materials that were collected and compiled systematically and then reviewed and analyzed qualitatively.Results of the Research: Company PT Amoeba Internasional have run company with binary system but in binary system the use pyramid scheme system by recruiting memers to join this scheme and as the number of people recruited increases, recruitment can no longer be done and most of the members can’t make a profit so in a pyramid scheme it only kills people who are above them and causes losses to members whojust joined or members who are below. As an effort to create protection for members in the MLM business system as well as create supervision and ethics in running a company with an MLM system, it has been regulated in the Regulation of the Minister of Trade of the Republik of Indonesia Number 70 of 2019 regarding the Direct Distribution of Goods and Supported by law Number 7 of 2014 concerning trade.